2012
DOI: 10.1007/s12031-012-9762-0
|View full text |Cite
|
Sign up to set email alerts
|

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a widespread neuropeptide with a diverse array of biological functions. Not surprisingly, the lack of endogenous PACAP therefore results in a variety of abnormalities. One of the important effects of PACAP is its neuroprotective and general cytoprotective role. PACAP protects neurons and other tissues against ischemic, toxic, and traumatic lesions. Data obtained from PACAP-deficient mice provide evidence that endogenous PACAP also has protective fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 84 publications
6
85
0
2
Order By: Relevance
“…These results are in agreement with the general observation that PACAP KO mice are more vulnerable to tissue injuries than wild type mice [ 59 ]. This is also true for ischemic injuries.…”
Section: Small Intestinal Ischemic Injury In Pacap Knockout (Ko) Micesupporting
confidence: 92%
“…These results are in agreement with the general observation that PACAP KO mice are more vulnerable to tissue injuries than wild type mice [ 59 ]. This is also true for ischemic injuries.…”
Section: Small Intestinal Ischemic Injury In Pacap Knockout (Ko) Micesupporting
confidence: 92%
“…in vivo decreased apoptosis, reduced expression of mcp-1, il-6, mip-2, myd88, tlr4, traf6, TRIF, IRF3 in primary mouse renal proximal tubule cells horvath et al [17] in vivo administration of pacap increased cell survival in primary rat kidney cell culture following H react more sensitively to various stressors [35], including ischemic lesions. pacap deficient mice displayed larger infarcted area in a model of focal cerebral ischemia and the extent of the ischemic retinal lesion was also increased [43].…”
Section: The Effect Of Endogenous Pacap In Ischemia/reperfusion-inducmentioning
confidence: 99%
“…it is suggested that endogenous pacap functions as a protective agent against different harmful stimuli [35,50]. Several studies have found that PACAP deficient mice Acta Biologica Hungarica 65, 2014 Table 1 summary of the protective effects of pacap in renal ischemia-reperfusion reference mode of investigation…”
Section: The Effect Of Endogenous Pacap In Ischemia/reperfusion-inducmentioning
confidence: 99%
“…PACAP knockout mice have decreased fertility, described in 82 numerous studies (Reglodi et al 2012a). This is in part due to 2003) in addition to other deficiencies described in mice 85 lacking endogenous PACAP (Reglodi et al 2012a).…”
mentioning
confidence: 99%
“…This is in part due to 2003) in addition to other deficiencies described in mice 85 lacking endogenous PACAP (Reglodi et al 2012a). antibodies, and membranes necessary for the measurements.…”
mentioning
confidence: 99%